Fabrication and characterization of microcrystalline cellulose from oil palm empty fruit bunch fiber reinforced polylactic acid composites - Norhafzan, Junadi (2020)
In this research, composites were prepared from microcrystalline cellulose (MCC) extracted from oil palm empty fruit bunch (EFB) fibre and poly (lactic) acid (PLA) polymer. Mechanochemical process which involves simultaneous alkali treatment assisted with ultrasonic process was implemented to isolate MCC from raw oil palm EFB fibre. Three steps have been used to prepare the MCC, namely removal of lignin, removal of hemicellulose and finally production of MCC. The MCC produced was further characterized by fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and also X-ray diffraction (XRD) measurement. The crystallinity index in MCC is found to be 81% which is higher than that of EFB fiber and cellulose. The degradation temperature, and the residue content revealed good thermal stability of MCC extracted through this mechanochemical technique. The optimization was done by using response surface methodology (RSM) in order to determine the optimum treatment condition of alkali concentration, ultrasonic temperature and ultrasonic exposure time towards the highest crystallinity of MCC produced. Composites were fabricated from MCC extracted reinforced poly lactic acid (PLA) polymer with different loading of MCC content (1, 3, 5 & 7 wt %) via a solution and casting method. Mechanical testing revealed that 5 wt % of MCC content in PLA exhibited the highest mechanical properties and this percentage was selected as the optimum fiber content for MCC/PLA based composite. Morphological analysis of MCC/PLA composites fractured surface by SEM revealed good adhesion of MCC with PLA. In order to improve mechanical properties of PLA and give better surface interaction between fibre and matrix, separate modifications were done to both fibre and matrix (i.e. MCC and PLA) respectively. Structural modification through chain extension and branching mechanism was done to improve the mechanical properties of PLA polymer while fiber surface treatment was done to improve the compatibility and the adhesion of MCC fibre. In PLA modification, Joncryl acts as a chain extender was incorporated into the PLA film with different loading (1, 3, and 5 wt%) and the characteristics of the modified PLA (Mod-PLA) films were characterized. 1 wt% of Joncryl content in PLA exhibited highest tensile strength (TS) and tensile modulus (TM) values but also led reduction in elongation at break. This percentage was selected as the optimum Joncryl content in modified PLA-based for further composite development study. In case of MCC modification, the MCC surface was incorporated by polyhedral oligomeric silsesquioxane (POSS) material with different percentage of POSS (5, 10 and 15 wt%). The modified MCC (POSS-MCC) were then characterized through structural, chemical interaction, morphological as well as thermal analysis. Morphological analysis of the modified MCC surface by FESEM revealed that POSS particles has been successfully grafted on it. Based on other characterization, it was found that the POSS-MCC improve the hydrophobicity of microcrystalline cellulose (MCC) but exhibit lower thermal properties in comparison with MCC. Fabrication of final composite was done by reinforced the modified MCC (POSS-MCC) into modified PLA matrix (Mod-MCC/Mod-PLA) and was further characterized. As conclusion from the comparative study of all the composites fabricated, Mod-MCC/Mod-PLA composite film exhibits improvement in both thermal properties and mechanical properties with highest TS, TM and elongation at break (EB) in comparison with other composites prepared along with the study development.